Improvement of Facial Skin Laxity by a Combined Technique With Hyaluronic Acid and Calcium Hydroxylapatite Fillers: A Clinical and Ultrasonography Analysis - Felix Bravo, Bruna Souza; Menezes Penedo, Lais Bezerra de; Carvalho, Raquel de Melo; Miot, Helio Amante [UNESP]; Elias, Mariana Calomeni (Journal Of Drugs In Dermatology, 2022)
Background: Facial aging involves skeletal changes, loss of volume in the fat compartment, and skin component changes. The current objective of cosmetic facial filling is to reestablish the overall aspect that was lost during the aging process. Hyaluronic acid (HA) and calcium hydroxyapatite (CaHA) fillers are indicated for facial rejuvenation, and these agents promote dissimilar effects regarding volume restoration and dermal biostimulation. Objective: This study aimed to assess clinical and ultrasonographic improvements in facial skin laxity using a technique that combines the injection of HA and CaHA. Methods: A 120-day follow-up, quasi -experimental study was conducted based on the enrollment of fifteen women (36-47 years old) with mild face flaccidity scores who underwent subcutaneous injection of up to 3 mL of HA (zygomatic-malar region, pyriform aperture, temporal region, and jaw) followed by 3 mL of 1:1 diluted CaHA using a fan technique (temporal, zygomatic-malar, and jaw regions). Objective: Adverse effects were registered, and the monthly assessed outcomes included clinical improvement, satisfaction, and high frequency ultrasonography (dermal thickness) parameters. Objective: Adverse effects were registered, and the monthly assessed outcomes included clinical improvement, satisfaction, and high frequency ultrasonography (dermal thickness) parameters. Results: At 120 days of follow-up, clinical assessment by blinded physicians yielded six (40%) very improved patients and nine (60%) exceptionally improved patients. All the participants were highly satisfied with the results and reported exceptional improvement. Dermal thickness increased 11.1 % (8.8-13.4%), and augmented dermal homogeneity was evidenced by ultrasonography. Local adverse effects were mild and transient. Conclusion: In conclusion, the combined technique with HA and CaHA fillers was well-tolerated and yielded high satisfaction and safe improve in facial skin laxity and dermal thickness in women with mild midface aging.